(untitled) (Shiksha Shastra Saurabh, 2018)
This article tries to focus on the role of English language in Nepal to uplift socioeconomic status tracing the shifts from historical practices, trends on academics, reviewing the status from policy practices and research trends. It tries to present the personal stories of learning English of professionals based on secondary source and reflecting the context of students from Nepal who desire to learn English. It tries to highlight the further suggestions and assumptions from Nepalese context in which role of English is studied in the socio-economic benefits.